Saudi Parents’ Involvement in Children’s Education during COVID-19 - Bahanshal, Dalal (Journal of Education and Training, 2022)
The flare-up of coronavirus has reportedly put on many changes and wrecked chaos in almost all life aspects, economically, academically, and socially. School closure has led to homeschooling, where the responsibility of children’s education was laid mainly in the parents’ hands. Consequently, many parents were compelled to be significantly involved in their children’s education. However, full parental engagement in children’s education is seemed to be a comparatively new trend amongst Saudi parents. Drawing from existing literature on parents’ involvement, this paper used a quantitative descriptive study through a survey method to access the experience of Saudi parents involved in homeschooling. A purposive sampling technique was used to recruit 51 Saudi parents. The findings showed that even though Saudi parents have encountered some challenges, they are facilitating their children’s learning and assisting them throughout the online learning process. Parents’ support was identified in different areas such as ensuring students’ attendance of online sessions, nurturing a good session flow, connecting with teachers and parents via WhatsApp group, and taking full responsibility for mongering their children during exams. The result provided a comprehensive set of recommendations not only to parents but also to schools to consolidate a good connection between especially in times of crisis. It is envisaged that the results of this study will enrich the literature about this phenomenon which seems relatively new not only in the context where this study was situated but worldwide due to the pandemic of coronavirus or other unforeseen circumstances.